Administration Timing Is the Best Clinical Outcome Predictor for Adalimumab Administration in Crohn's Disease - Mastronardi, Mauro; Curlo, Margherita; Cavalcanti, Elisabetta; Burattini, Osvaldo; Cuppone, Renato; Tauro, Romina; De Santis, Stefania; Serino, Grazia; Pesole, Pasqua Letizia; Stasi, Elisa; Caruso, Maria Lucia; Donghia, Rossella; et al. (Frontiers in Medicine, 2019)
Biological intervention for Crohn's Disease (CDs) patients, mainly using anti-TNF antibodies, is often an efficient therapeutic solution. Nonetheless, data defining the administration timing to maximize the chances of clinical remission are lacking. The objective of this “real-life” retrospective study was to evaluate if early Adalimumab (ADA) administration (<12 months) was an efficient strategy to improve patients' clinical outcome. This single center study included 157 CD patients, of which 80 received the first ADA administration within the first 12 months from the diagnosis. After 1 year of therapy, clinical remission was observed in 50.32% of patients, mucosal healing in 37.58%. Clinical remission was observed in 66.25% of the early ADA administration patients vs. 33.77% of the late (>12 months) (p < 0.001); mucosal healing was observed in 53.75% of the early vs. 20.78% of the late (p < 0.001). Dose escalation was required for 30.00% of the early vs. 66.23% of the late (<0.01). In the early ADA administration group, 7.50% patients were considered non-responders at the end of the follow-up vs. 22.08% patients in the late administration group. These findings highlighted that early ADA administration (within 1 year of diagnosis) improves the clinical response and mucosal healing, and reduces the loss of response rate and need for dose escalation.